2022
DOI: 10.1108/jfrc-11-2021-0092
|View full text |Cite
|
Sign up to set email alerts
|

Financial inclusion for women empowerment in South Asian countries

Abstract: Purpose This paper aims to address the issues of Asian countries toward why females are discouraged and more likely to be removed from the formal financial system than males. Further, whether there is any connection between religion and women’s financial inclusion is also addressed. Design/methodology/approach This paper explores gender disparities in the use of structured financial services through multilevel models tailored to the individual. The data from 2004 to 2017 have been used for eight South Asian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 51 publications
1
11
0
Order By: Relevance
“…Based on the information found from the extensive literature review, it has been clearly understood that for SWE and sustainable economic growth, the FI of poor women and bridging the BoP with the formal financial system are very important. Furthermore, the FI EDI 42,1 and AC are highly influenced by the social, economic and individual characteristics of borrowers (Agnello et al, 2012;Aziz et al, 2022;Datta and Sahu, 2022;Kaur and Kapuria, 2020;Malik et al, 2021). Though the researchers observed these social, economic and individual determinants of FI in different contexts in different cultures, we have not found any single study in which a complete framework has been observed.…”
Section: Methodsmentioning
confidence: 76%
See 3 more Smart Citations
“…Based on the information found from the extensive literature review, it has been clearly understood that for SWE and sustainable economic growth, the FI of poor women and bridging the BoP with the formal financial system are very important. Furthermore, the FI EDI 42,1 and AC are highly influenced by the social, economic and individual characteristics of borrowers (Agnello et al, 2012;Aziz et al, 2022;Datta and Sahu, 2022;Kaur and Kapuria, 2020;Malik et al, 2021). Though the researchers observed these social, economic and individual determinants of FI in different contexts in different cultures, we have not found any single study in which a complete framework has been observed.…”
Section: Methodsmentioning
confidence: 76%
“…Furthermore, the FI and AC are highly influenced by the social, economic and individual characteristics of borrowers (Agnello et al. , 2012; Aziz et al. , 2022; Datta and Sahu, 2022; Kaur and Kapuria, 2020; Malik et al.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to a lack of income and knowledge, women are disempowered. Women empowerment is required to manage this issue of cultural limitations and gender discrimination and allow them to live their lives freely (Aziz et al , 2022; Laila, 2006). Financial inclusion is important in empowering women and assisting them in overcoming the obstacles they face.…”
Section: Literature Reviewmentioning
confidence: 99%